Advanced nutrition and dietetics in gastroenterology - Lomer, Miranda (Advanced nutrition and dietetics book series, 2014)
-First title in new series from the British Dietetic Association: each title isa comprehensive and critical review of key literature in its subject -Provides informative and broad-ranging coverage of the relation between nutrition and diet and the gastrointestinal tract -Explores dietary factors involved in a range of gastrointestinal disorders, plus effects on diet and available treatments -Trustworthy, internationally-focused, and written specifically to meet the needs of dietitians.